2016
DOI: 10.1016/j.jbiomech.2016.04.039
|View full text |Cite
|
Sign up to set email alerts
|

High seeding density of human chondrocytes in agarose produces tissue-engineered cartilage approaching native mechanical and biochemical properties

Abstract: Animal cells have served as highly controllable model systems for furthering cartilage tissue engineering practices in pursuit of treating osteoarthritis. Although successful strategies for animal cells must ultimately be adapted to human cells to be clinically relevant, human chondrocytes are rarely employed in such studies. In this study, we evaluated the applicability of culture techniques established for juvenile bovine and adult canine chondrocytes to human chondrocytes obtained from fresh or expired oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 60 publications
1
47
0
Order By: Relevance
“…While a few studies have characterized the frictional and shear properties of tissue engineered articular cartilage constructs cultured with bovine or porcine cells, this study is the first to perform such analysis on human chondrocyte‐seeded implants. Additionally, only a few previous studies have characterized the compressive properties of human chondrocyte seeded implants . Overall, the results of this study provide a deeper understanding of the spectrum of mechanical behavior exhibited by tissue engineered human articular cartilage.…”
Section: Discussionmentioning
confidence: 79%
“…While a few studies have characterized the frictional and shear properties of tissue engineered articular cartilage constructs cultured with bovine or porcine cells, this study is the first to perform such analysis on human chondrocyte‐seeded implants. Additionally, only a few previous studies have characterized the compressive properties of human chondrocyte seeded implants . Overall, the results of this study provide a deeper understanding of the spectrum of mechanical behavior exhibited by tissue engineered human articular cartilage.…”
Section: Discussionmentioning
confidence: 79%
“…69 The current study, in tandem with our recent and promising results from constructs seeded with young and adult human chondrocytes (ages 17 to 35), suggests that engineering articular surfacesized constructs with human cells is a feasible strategy for treating advanced OA. 49 Study 1 showed that premature channel filling was detrimental to constructs (Fig. 4C, D and 5C), whereas Study 2 constructs with repunched channels exhibited the highest functional properties (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…12,[74][75][76][77] With regard to (b), we have recently observed that young adult human chondrocytes, isolated from expired osteochondral allografts from a tissue bank, exhibit chondrogenic potential nearly comparable to that of immature bovine chondrocytes. 49 Therefore, we plan to further investigate this source of human cells in our effort to translate our tissue engineering approach to the clinic.…”
Section: Fig 9 Study 2 Construct Functional Properties: (A) E Y (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, juvenile chondrocytes have shown promise for clinical applications in allogeneic transplantation (Adkisson et al, 2010). Ongoing and future studies by our group seek to translate results in bovine model systems to human chondrocytes (Cigan et al, 2016; O'Connell et al, 2015). …”
Section: Discussionmentioning
confidence: 99%